THE BASTARDIZATION OF ISLAMIC LAW BY THE SOUTH AFRICAN COURTS - Razaana Denson; Marita Carnelley; Andre Mukheibir (Obiter, 2018)
Notwithstanding the fact that South Africa is a country rich in cultural diversity, and despite section 15 of the Constitution, the recognition of systems of religious, personal or family law for certain cultural and religious groups has either been limited or is virtually non-existent. This is particularly true in the case of Muslim marriages. To this extent, marriages concluded in terms of Islamic rites do not enjoy the same legal recognition that is accorded to civil and customary marriages. Non-recognition of Muslim marriages has dire consequences for the parties to the marriage, more so for women who are parties to Muslim marriages as there is no legal regulatory framework to enforce any of the consequences that arise as a result of the marriage. Therefore, in most cases, parties to a Muslim marriage are left without adequate legal protection, where the marriage is dissolved either by death or divorce. The non-recognition of Muslim marriages effectively means that despite the fact that the parties to a Muslim marriage may regard themselves as married, there is no legal connection between them. Despite South Africa’s commitment to the right of equality and freedom of religion, the courts have acknowledged that the failure to grant recognition to Muslim marriages on the ground of gender equality, has worsened the plight of women in these marriages, in that they were left without effective legal protection during the subsistence of the marriage and also when the marriage is dissolved either by death or divorce. Whilst the ad hoc recognition of certain consequences of Muslim marriages by the judiciary has gone some way to redress the plight of Muslim women and provided relief to the lived realities of Muslim women, these decisions are in fact contrary to the teachings and principles of Islam and therefore problematic for Muslims. These court decisions that are in conflict with Muslim Personal Law (MPL) will ultimately lead to the emergence of a distorted set of laws relating to Muslim family law. This is a real cause for concern. A discussion of these cases is undertaken in this article.